2020
DOI: 10.1002/nau.24431
|View full text |Cite
|
Sign up to set email alerts
|

Functional heterogeneity of PDGFRα (+) cells in spontaneously active urogenital tissues

Abstract: Aims As PDGFRα (+) cells appear not to suppress the excitability of detrusor smooth muscle by generating SK3‐dependent hyperpolarising as proposed in the gastrointestinal tract, we further explored the functional roles of PDGFRα (+) cells in regulating the spontaneous activity of urogenital tissues. Methods Using PDGFRα‐eGFP mice, intracellular Ca2+ signaling in PDGFRα (+) cells of the bladder lamina propria, renal pelvis, and seminal vesicle were visualized using Cal‐590 fluorescence. The distribution and SK3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…ASMCs are most abundant in the proximal RP, at the PKJ ( Figure 1A – C ), where peristaltic contractions and electrical pacemaker activity originates 5 , 7 , 8 , 9 , 12 , 13 , 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 . A recently published study by this group identified platelet-derived growth factor receptor-alpha (PDGFRα), in combination with smooth muscle myosin heavy chain (smMHC), as a unique biomarker for these interstitial cells (ICs) 24 , a finding that has been corroborated by other groups 25 . Based on their morphology and protein expression pattern, these cells were called PDGFRα + IC type 1 (PIC1) 24 , 26 .…”
Section: Introductionmentioning
confidence: 78%
“…ASMCs are most abundant in the proximal RP, at the PKJ ( Figure 1A – C ), where peristaltic contractions and electrical pacemaker activity originates 5 , 7 , 8 , 9 , 12 , 13 , 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 . A recently published study by this group identified platelet-derived growth factor receptor-alpha (PDGFRα), in combination with smooth muscle myosin heavy chain (smMHC), as a unique biomarker for these interstitial cells (ICs) 24 , a finding that has been corroborated by other groups 25 . Based on their morphology and protein expression pattern, these cells were called PDGFRα + IC type 1 (PIC1) 24 , 26 .…”
Section: Introductionmentioning
confidence: 78%
“…ASMCs are most abundant in the proximal RP, at the PKJ (Figure 1A-C), where peristaltic contractions and electrical pacemaker activity originates 5 , 7 , 8 , 9 , 12 , 13 , 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 . A recently published study by this group identified platelet-derived growth factor receptor-alpha (PDGFRα), in combination with smooth muscle myosin heavy chain (smMHC), as a unique biomarker for these interstitial cells (ICs) 24 , a finding that has been corroborated by other groups 25 . Based on their morphology and protein expression pattern, these cells were called PDGFRα + IC type 1 (PIC1) 24 , 26 .…”
Section: Introductionmentioning
confidence: 78%
“…Indeed, functional heterogeneity of PDGFRα + cells is becoming evident in various urogenital organs. In the mouse bladder, stimulation of P2Y 1 receptors induces Ca 2+ transients in PDGFRα + interstitial cells, which did not suppress the LVDCC-dependent spontaneous Ca 2+ transients in the neighbouring detrusor SMCs (Hayashi et al 2019;Hashitani et al 2020). In the renal pelvis, spontaneously active PDGFRα + ASMCs depolarise the membrane of adjacent typical SMCs to induce action potential generation suggesting that PDGFRα + ASMCs act as the pacemaker cells for pyeloureteric peristalsis (Grainger et al 2020;Hashitani et al 2020).…”
Section: Asynchronous Spontaneous Ca 2+ Transients and Stds In Becs O...mentioning
confidence: 89%
“…2020; Hashitani et al . 2020). Therefore, it is of great interest to know if PDGFRα + cells in the SV mucosa may also develop depolarising signals and function as pacemaker cells for SPCs of SV smooth muscle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation